Assessing Factors Affecting Local Government Service Delivery: A Case of Chingola, Kitwe and Ndola City Councils in Zambia - Hang’andu, Claudia Monde; Banda, Matthew K (Archives of Business Research, 2024)
The UN HABITAT, (2022) estimated the 1.5 million housing deficit in Zambia is expected to reach 3.3 million by 2030. The projected housing deficit led to the examination of factors influencing home ownership among public servants. While there is substantial research on homeownership in advanced economies, little is documented on the Zambian scene. The study focuses on home ownership among public sector employees drawn from a population of teachers in public schools. Using a mixed approach, the study collected data from a sample of 390. The results revealed that individual attitude, housing need and financial factors have significant influence on homeownership whereas family influence did not. Financial factors have the greatest influence on homeownership among the public workers. The study suggests offering affordable financing options for home ownership, making home construction land affordable and available, facilitating the purchase of building supplies through building societies, and finally educating the general public about land and home ownership.